Empowering Youth through Innovation in AR Media: Implications for Achieving the SDGs - Sicha, Ainus; Putri, Amalia Rosyadi; Atikoh, Nurul; Hidayat, Maulana Wahyu; Rohmana, Devie Wianda; Baharuddin, Ahmad Muharya (Universitas Muhammdiyah Yogyakarta, 2026)
The rapid growth of digital technology presents both opportunities and challenges for youth empowerment, particularly in developing relevant skills and shaping professional identity in the digital era. However, existing studies often focus on fragmented skill development, with limited attention to integrated empowerment processes within a sustainable ecosystem. This study aims to examine how AR Media facilitates youth empowerment through an ecosystem-based approach that integrates skill development, professional identity formation, and social engagement. This research employs a qualitative case study approach, using observations, interviews, and document analysis involving participants in AR Media programs. The findings show that empowerment occurs through a structured transformation process in which key inputs such as technology, mentorship, and participation are developed into outputs including digital competencies, communication skills, and professional networks. These outputs further lead to broader outcomes, particularly the development of adaptive, confident, and socially engaged youth. The study proposes an integrative ecosystem-based empowerment model as its main contribution, offering a holistic perspective that links knowledge, adaptive skills, identity formation, and social engagement. This study contributes to SDG 4, SDG 8, SDG 9, and SDG 17 by demonstrating how ecosystem-based learning enhances youth readiness for the future of work and supports inclusive and sustainable development.